Chapter 3: Noongar boordier gnulla katitjin – The influence of Noongar knowledge. - Buchanan, J.; Collard, Len; Cumming, Ingrid; Palmer, D.; Scott, Kim; Hartley, John (Cultural Science, 2016)
Despite the history of settler colonisation and state control (Attwood, 1989), where Indigenous people and their knowledge has been ‘classified, excluded, objectified, individualised, disciplined, and normalised’ (Best and Kellner), it is important to recognise that this is not the complete story. Western science and knowledge systems have had a long history of interrelationship with Australian Indigenous cultural life and systems. As bell hooks (1992) put it when describing the influence of African-Americans on US culture (see also Todd Boyd, 1997), even in the worst circumstances of domination, blacks have an ability to manipulate, shape and open up exchanges with white knowledge systems.